2021
DOI: 10.1093/heapol/czab026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of campaign-style delivery of routine vaccines: a quasi-experimental evaluation using routine health services data in India

Abstract: The world is not on track to achieve the goals for immunization coverage and equity described by the World Health Organization’s Global Vaccine Action Plan. Many countries struggle to increase coverage of routine vaccination, and there is little evidence about how to do so effectively. In India in 2016, only 62% of children had received a full course of basic vaccines. In response, in 2017–18 the government implemented Intensified Mission Indradhanush (IMI), a nationwide effort to improve coverage and equity u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…A survey study showed an increase in full immunization rates in IMI districts 12 . Another new study used administrative data on vaccine doses delivered and found increased delivery of doses to IMI districts during the intervention period for 13 vaccines, but reduced volume of vaccine delivery at the end of IMI 14 . This suggests that further research is needed to evaluate the longer‐term effects of PIRI activities.…”
Section: Discussionmentioning
confidence: 99%
“…A survey study showed an increase in full immunization rates in IMI districts 12 . Another new study used administrative data on vaccine doses delivered and found increased delivery of doses to IMI districts during the intervention period for 13 vaccines, but reduced volume of vaccine delivery at the end of IMI 14 . This suggests that further research is needed to evaluate the longer‐term effects of PIRI activities.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization special drives such as Mission Indradhanush and Intensified Mission Indradhanush have succeeded in increasing vaccination rates in underserved districts ( Gurnani et al. , 2018 ; Clarke-Deelder et al. , 2021 ; Summan et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2018 ; Clarke-Deelder et al. , 2021 ), but this effect did not persist 8 months after implementation ( Clarke-Deelder et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations